Uso de indicadores para a análise ambiental na unidade de conservação apa Serra Branca - Ba - Alves, Adriano Almeida (2018)
The creation of Conservation Units has been showing the most widespread idea in our current conception of nature conservation, mainly with the various transformations that occurred in the second half of the twentieth century. The Environmental Protection Areas (APA) are an example of Conservation Units, as is the case of APA Serra Branca, a Sustainable Use Conservation Unit. There are several criteria used for the delimitation of a Conservation Unit, and the risk of environmental vulnerability is one of them, so this work aimed to analyze the environmental vulnerability of the APA Serra Branca through environmental indicators for the elaboration of an Environmental Zoning, using variables that point out and quantify vulnerable areas as a means of responding if environmental indicators are capable of measuring environmental vulnerability, making it possible to infer about environmental sustainability and the possible fragilities and potentialities of the area. The application of geoprocessing techniques subsidized the analysis and integration of data and information, as well as the generation of products, such as cartographic. It was these techniques that made it possible to obtain the results such as: Map of Critical Areas; Modeling of the Environmental Vulnerability of the APA Serra Branca and Environmental Zoning of the APA Serra Branca. In order to define the critical areas, the criteria proposed by Bessa Junior and Muller were taken into account, taking into account environmental indicators (Hypsometry, Declivity, Hydrography) that were crossed through the intersection with the land Use and Coverage map. The modeling developed was based on criteria adapted from Crepani to local reality. The map of environmental vulnerability derived from map algebra related to the themes: Land Declivity, Use and Coverage, Geomorphology, Geology and Soils, for each variable, a vulnerability value was inserted through a map reclassification technique. As a final result, the Environmental Zoning was generated, which was derived from the intersection of the Environmental Vulnerability map with the Land Use and Coverage map. At the end of these stages, it was possible to observe the areas with greater environmental vulnerability, and the areas that were more stable, which represented the greater part of the APA Serra Branca area